Biliverdin Reductase A Protects Lens Epithelial Cells against Oxidative Damage and Cellular Senescence in Age-Related Cataract. (19th July 2022) - Huang, Yang; Liu, Ying; Yu, Siwei; Li, Wenzhe; Li, Jinglan; Zhao, Bo; Hu, Xin; Jin, Haiying
Abstract : Age-related cataract (ARC) is the common cause of blindness globally. Reactive oxygen species (ROS), one of the greatest contributors to aging process, leads to oxidative damage and senescence of lens epithelial cells (LECs), which are involved in the pathogenesis of ARC. Biliverdin reductase A (BVRA) has ROS-scavenging ability by converting biliverdin (BV) into bilirubin (BR). However, little is known about the protective effect of BVRA against ARC. In the present study, we measured the expression level of BVRA and BR generation in human samples. Then, the antioxidative property of BVRA was compared between the young and senescent LECs upon stress condition. In addition, we evaluated the effect of BVRA on attenuating H2 O2 -induced premature senescence in LECs. The results showed that the mRNA expression level of BVRA and BR concentration were decreased in both LECs and lens cortex of age-related nuclear cataract. Using the RNA interference technique, we found that BVRA defends LECs against oxidative stress via (i) restoring mitochondrial dysfunction in a BR-dependent manner, (ii) inducing heme oxygenase-1 (HO-1) expression directly, and (iii) promoting phosphorylation of ERK1/2 and nuclear delivery of nuclear factor erythroid 2-related factor 2 (Nrf2). Intriguingly, the antioxidative effect of BVRA was diminished along with the reduced BR concentration and repressed nuclear translocation of BVRA and Nrf2 in senescent LECs, which would be resulted from the decreased BVRA activity and impaired nucleocytoplasmic trafficking. Eventually, we confirmed that BVRA accelerates the G1 phase transition and prevents against H2 O2 -induced premature senescence in LECs. In summary, BVRA protects LECs against oxidative stress and cellular senescence in ARC by converting BV into BR, inducing HO-1 expression, and activating the ERK/Nrf2 pathway. This trial is registered with ChiCTR2000036059 .